Sharia Crowdfunding as an Instrument of MSME Financial Inclusion in Indonesia: Development, Challenges, and Regulatory Implications - Bunga Dwi Fani Ritonga; Saparuddin Siregar; Maryam Batubara (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Sharia crowdfunding has gained increasing attention as an alternative financing mechanism capable of supporting MSME financial inclusion in Indonesia’s Islamic economic framework. This study aims to analyze the development of Sharia crowdfunding, identify key challenges in its implementation for MSME financing, and examine the resulting regulatory and institutional implications. Employing a qualitative research approach, the study utilizes in-depth interviews, document analysis, and literature review to capture perspectives from regulators, platform operators, Sharia authorities, investors, and MSME actors. The findings indicate that Sharia crowdfunding contributes to expanding access to capital through ethical, risk-sharing, and technology-based financing models, while remaining consistent with Islamic principles. However, its implementation is constrained by limited financial literacy, dual regulatory compliance demands, governance standardization issues, MSME capacity limitations, and investor risk perceptions. The study further reveals that effective regulatory harmonization, strengthened Sharia supervision, and institutional coordination are critical to ensuring sustainability and credibility. These findings underscore the role of Sharia crowdfunding as a complementary instrument for inclusive economic development and provide policy-relevant insights for strengthening Indonesia’s Islamic fintech ecosystem.